2016
DOI: 10.1016/j.jalz.2016.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Life‐course blood pressure in relation to brain volumes

Abstract: INTRODUCTION The impact of blood pressure on brain volumes may be time- or pattern-dependent. METHODS In 1678 participants from the Atherosclerosis Risk in Communities Neurocognitive Study, we quantified the association between measures and patterns of blood pressure over three time points (~24 or ~15 years prior and concurrent with neuroimaging) with late life brain volumes. RESULTS Higher diastolic blood pressure ~24 years prior, higher systolic and pulse pressure ~15 years prior, and consistently elevat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 32 publications
0
57
0
Order By: Relevance
“…The notion that cardiovascular disease during midlife influences late-life neurologic outcomes has been borne out in recent epidemiological literature 19,20 . Although we found associations between midlife CRP levels and late-life white matter structural abnormalities that were independent of midlife cardiovascular disease, it remains possible that these associations are mediated, at least in part, by interim cardiovascular disease occurring after midlife.…”
Section: Discussionmentioning
confidence: 99%
“…The notion that cardiovascular disease during midlife influences late-life neurologic outcomes has been borne out in recent epidemiological literature 19,20 . Although we found associations between midlife CRP levels and late-life white matter structural abnormalities that were independent of midlife cardiovascular disease, it remains possible that these associations are mediated, at least in part, by interim cardiovascular disease occurring after midlife.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic hypertension also compromises blood-brain barrier (BBB) integrity, leading to both cerebral edema and the introduction of systemic elements into the brain parenchyma [49]. Hypertension recorded 15 years prior has been associated with smaller brain volumes in areas typically affected by AD such as the hippocampus [50]. Our group has observed that an increased resting-state cardiac rate pressure product as a surrogate of myocardial oxygen use has a small to moderate correlation with neocortical amyloidosis in midlife adults with preclinical AD [51].…”
Section: Hypertension/hypotensionmentioning
confidence: 99%
“…In elderly populations, low SBP [116,117] and low DBP [117,118] have been associated with reduced brain volume and cortical thickness, suggesting that the relationship between BP and brain volume may age-dependent [15,119,120]. A pattern of hypertension in midlife followed by hypotension in late-life appears to be especially harmful [34], particularly in brain regions affected in the earliest phase of Alzheimer’s disease [121]. …”
Section: Pathophysiology Of Hypertension As It Relates To Cognitive Dmentioning
confidence: 99%
“…Not only do these vascular changes shift the cerebral autoregulatory curve in a manner which reduces resting cerebral blood flow, but the brain also becomes more susceptible to hypoperfusion during periods of low systemic BP [152] or during periods of normal BP in chronically hypertensive individuals [153]. These hypertension-induced changes to cerebral autoregulation and perfusion may explain why individuals with chronic hypertension in midlife and low BP in late-life show significant reductions in brain volume [34,121] and greater levels of cognitive deficits [101]. …”
Section: Pathophysiology Of Hypertension As It Relates To Cognitive Dmentioning
confidence: 99%